2024
DOI: 10.1186/s13000-024-01457-6
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-positive inflammatory follicular dendritic cell sarcoma with significant granuloma: case report and literature review

Chenchen Nie,
Xun Xie,
Hangyan Li
et al.

Abstract: Background Epstein-Barr virus-positive inflammatory follicular dendritic cell sarcoma (EBV+IFDCS) is a rare disease characterized by mild clinical symptoms and non-specific imaging findings. The diagnosis of the disease depends on pathological diagnosis. However, EBV+IFDCS has a very broad spectrum of histological morphology and immune phenotypes, and its histopathological features have not been fully described by pathologists. Case presentation A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In a Korean study [ 16 ], a large number of IgG4-positive plasma cells were found in six EBV-positive patients with IPT-like FDCS, suggesting that EBV has a key role in IPT-like FDCS. Three cases of IPT-like FDCS, characterized by IgG4 positivity, EBV positivity, and splenic involvement, were also reported in various studies [ 8 , 14 , 17 ]. Additional markers for FDCS encompass Ki-M4 and CD14 [ 35 ], CXCL13 and clusterin [ 36 ], gamma-synuclein and D2-40 [ 8 , 16 ], podoplanin and the low affinity NGFR [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In a Korean study [ 16 ], a large number of IgG4-positive plasma cells were found in six EBV-positive patients with IPT-like FDCS, suggesting that EBV has a key role in IPT-like FDCS. Three cases of IPT-like FDCS, characterized by IgG4 positivity, EBV positivity, and splenic involvement, were also reported in various studies [ 8 , 14 , 17 ]. Additional markers for FDCS encompass Ki-M4 and CD14 [ 35 ], CXCL13 and clusterin [ 36 ], gamma-synuclein and D2-40 [ 8 , 16 ], podoplanin and the low affinity NGFR [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 79%
“…IPT-like FDCS typically follows a painless course and exhibits a more indolent nature compared to classic FDCS. It was noted that IPT-like FDCS exhibits an inert biological behaviour that allows patients to achieve long-term survival even in the event of relapse [ 14 ]. Our findings corroborate this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation